Transgender Entrepreneurs’ Level Of Awareness Towards Government Services And Programs For Transgenders And Entrepreneurs (Journal of Namibian Studies : History Politics Culture, 2022)
Entrepreneur is an individual who captivating on financial threat or startup a business in the hope of profit. Despite the fact that, third gender plays a vital position in the social order motionless their entrepreneurial capabilities have not been properly tapped owing to the substandard position of, Transgender in Indian society. In today’s world, third gender entrepreneurs also play a very important role in local business background and it is really significant for the unstoppable financial and social development. Both central and state Government considering the significance of Transgender entrepreneurship and their contribution towards country’s growth and prospects, has introduced a lot of schemes for promoting entrepreneur in general, especially for third gender. The study could establish the Transgender entrepreneurs’ level of awareness of government schemes and programs for Transgender community. This study was made an attempt to determine the Transgender entrepreneurs’ level of awareness towards government schemes and programs. Data was collected from 188 respondents through interview schedule. SPSS 20 has been used to analyze and interpret data. T-test, ANOVAs and chi-square analysis have been used. Study results show that customers are not fully aware also about the government schemes and programs; as a result government should create consciousness through organizing different workshops/seminars for making Transgender entrepreneurs well aware.